DEVELOPMENT OF METHODS OF FINANCIAL SUPPORT FOR INVESTMENTS - Zoya Shapiulahovna BABAEVA; Yuriy Ivanovich SIGIDOV; Sergey Vladimirovich DOKHOLYAN; Elnara Migaxhidinovna EMINOVA; Rustam Alievich YALMAEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The growth of the investment activity in the Russian agro-industrial complex (AIC) is substantiated by the specificity of the agro-industrial production, the functioning of which is related to overcoming the following systemic problems: underdevelopment of infrastructure facilities, shortage of qualified production and management personnel, and a low level of developing scientifically grounded economic forms. The article introduces methods for supporting the AIC investment activity, including the economic methods that were recognized as the most preferable ones. The following instruments that have a direct financial influence in the taxation, credit-and-monetary, budgetary and external economic areas have been defined within economic methods: provision of tax credits for the placed investments (so-called tax credit); provision of tax incentives and special tax regimes for investors at AIC enterprises; accelerated depreciation of fixed capital; targeted lending of AIC enterprises for investment purposes; subsidies and subventions from local budgets for AIC enterprises; forming and funding of AIC investment projects from regional budgets; provision of budgetary guarantees to AIC private investors; attracting foreign investment in the region AIC; provision of privileges (taxation, lending) to AIC enterprises that participate in the foreign economic activity, etc. The sequence of organizing investment processes in AIC is shown. The normative and legal support for the AIC investment activity in the form of a three-level system of normative acts is given.